2015
DOI: 10.1021/acs.jafc.5b04223
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Profiling and Enzyme Analyses Indicate a Potential Role of Antioxidant Systems in Complementing Glyphosate Resistance in an Amaranthus palmeri Biotype

Abstract: Metabolomics and biochemical assays were employed to identify physiological perturbations induced by a commercial formulation of glyphosate in susceptible (S) and resistant (R) biotypes of Amaranthus palmeri. At 8 h after treatment (HAT), compared to the respective water-treated control, cellular metabolism of both biotypes were similarly perturbed by glyphosate, resulting in abundance of most metabolites including shikimic acid, amino acids, organic acids and sugars. However, by 80 HAT the metabolite pool of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
106
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(129 citation statements)
references
References 53 publications
20
106
2
1
Order By: Relevance
“…In particular, in untreated plants, the level of free AAA content was similar in GR and GS populations ( Figure 5 ). Similar AAA content in glyphosate resistant/sensitive biotypes has been previously described ( Maroli et al, 2015 ). This is consistent with previous reports suggesting that the overexpression of EPSPS may have no fitness cost in A. palmeri ( Giacomini et al, 2014 ; Vila-Aiub et al, 2014 ).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In particular, in untreated plants, the level of free AAA content was similar in GR and GS populations ( Figure 5 ). Similar AAA content in glyphosate resistant/sensitive biotypes has been previously described ( Maroli et al, 2015 ). This is consistent with previous reports suggesting that the overexpression of EPSPS may have no fitness cost in A. palmeri ( Giacomini et al, 2014 ; Vila-Aiub et al, 2014 ).…”
Section: Discussionsupporting
confidence: 83%
“…PAL activity was carried out according to Orcaray et al (2011) with the following modifications. Samples were immediately centrifuged after extraction (12,000 g , 5 min) The reaction was started by the addition of 25 mM L -phenylalanine ( Maroli et al, 2015 ). Controls (without L -phenylalanine) were prepared to determine endogenous levels of transcinnamic acid (t-CA).…”
Section: Methodsmentioning
confidence: 99%
“…Although several short-term biochemical studies have been published recently [17][18][19][20], the originality of this study involves the wide time span used, covering a full period from the initial phases (when plants did not look affected) until when they were visually injured. The measurements performed in this work at the different phases of the treatment (days 1 and 3) and the continuation for 15 days allowed evaluation of the pattern of the shikimate pathway from the onset of the treatment until severe injury.…”
Section: Resultsmentioning
confidence: 99%
“…Previous findings showed that both AHAS and EPSPS inhibitors cause growth arrest followed by a slow plant death of the herbicide-treated plants although they act upon different pathways [5,6]. Both types of herbicides provoke an accumulation of free amino acids [3,[7][8][9][10][11]. This effect is accompanied by a decrease in the soluble protein content [9,11,12] and may be the key to the common response that has been associated with a plant proteolysis response [9].…”
Section: Introductionmentioning
confidence: 99%